2010
DOI: 10.1109/tnsre.2009.2034162
|View full text |Cite
|
Sign up to set email alerts
|

Universal Haptic Drive: A Robot for Arm and Wrist Rehabilitation

Abstract: In this paper we present a universal haptic drive (UHD), a device that enables rehabilitation of either arm ("ARM" mode) or wrist ("WRIST" mode) movement in two degrees-of-freedom. The mode of training depends on the selected mechanical configuration, which depends on locking/unlocking of a passive universal joint. Actuation of the device is accomplished by utilizing a series elastic actuation principle, which enables use of off-the-shelf mechanical and actuation components. A proportional force control scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 25 publications
0
74
0
4
Order By: Relevance
“…The human hand has many joints and performs important functions; therefore, injury to or loss of fingers is a serious problem. Prosthetic hands [7][8][9][10][11][12] and robotic devices that assist rehabilitation [13][14][15][16][17][18][19][20][21][22][23][24][25][26] are being developed in many institutes, and some prosthetic hands are available in the world market [7][8][9]. Robotic devices that assist rehabilitation are helpful in achieving an early recovery for injured patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human hand has many joints and performs important functions; therefore, injury to or loss of fingers is a serious problem. Prosthetic hands [7][8][9][10][11][12] and robotic devices that assist rehabilitation [13][14][15][16][17][18][19][20][21][22][23][24][25][26] are being developed in many institutes, and some prosthetic hands are available in the world market [7][8][9]. Robotic devices that assist rehabilitation are helpful in achieving an early recovery for injured patients.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic devices that assist rehabilitation are helpful in achieving an early recovery for injured patients. Devices that target the upper limb (shoulder or elbow, without hand) are currently being researched [13][14][15][16][17][18][19], while other work focuses on hand and finger function [20][21][22][23][24][25][26]. While research on prosthetic hardware has achieved a certain level, the next step must focus on how to control these devices.…”
Section: Introductionmentioning
confidence: 99%
“…When the handle is oriented horizontally, the second DOF is extension/flexion (Figure 6(d) and 6(e)), and when the handle is oriented vertically, the second DOF is radial/ulnar deviation (Figure 6(f) and 6(g)), respectively. Comparisons between achievable ROM of the UHP in Wrist mode and the human wrist have been previously shown [27]. Note that in this mode, a change in length of the segment below universal joint lock A occurs because of the fixed position of the wrist gimbal.…”
Section: Wrist Mode-lock Configuration Bcmentioning
confidence: 85%
“…While the UHP uses the same series elastic actuators (SEAs) as used in the UHD (SEA also described by Oblak et al [27]), the modification can be found in a pantograph mechanism and system of configurable joint locks that can more efficiently transition between five distinct modes of operation with minimal effort by the therapist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation